Pengaruh Regret Aversion Bias dan Overconfidence Terhadap Pengambilan Keputusan Investasi Cryptocurrency Pada Investor Generasi Milenial - Ema Nursalimah; Indah Utami (Robust: Research of Business and Economics Studies, 2022)
The aim of this study is to investigate the effect of regret-aversion bias and overconfidence on millennial investors' cryptocurrency investment decisions. The population in this study are people from Sumatra, Java, and Nusa Tenggara (Bali) who have invested in or only know about cryptocurrencies. For the sampling technique of this study using the Objective Sampling method for a population of 35 people. The method used in this study is a quantitative method using primers which were analyzed by Path Analysis using the Smart Pls 3.0 program. The results obtained in this study indicate that regret-avoidance bias has no significant effect on investment decision making, while overconfidence has a significant effect on investment decision making.